1977
DOI: 10.1002/qua.560110115
|View full text |Cite
|
Sign up to set email alerts
|

Conformational profile of nalorphine by PCILO calculations

Abstract: The substitution of an ally1 group for the methyl group on the nitrogen of morphine changes the pharmacological activity from that of a narcotic agonist to that of a mixed narcotic agonist-antagonist; substitution of an allyl group for the methyl group in oxymorphone changes it from a narcotic agonist to a pure antagonist [ I]. (The molecular structures are depicted in Figure 1.) When we first initiated our quantum chemical investigations on narcotics and narcotic antagonists [2] there was no structural inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1979
1979
2009
2009

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Ordinarily if there has been a crystal structure determined for a medium or large drug or biomolecule molecule, we initiate our quantum chemical calculations at the molecular geometry as determined in the crystal. Our prior experience [20,21] has indicated that for most molecules of this type, especially ones whose structure is composed primarily of ring skeletons, the major influence on molecular structure is intramolecular rather than crystal packing or intermolecular forces. The molecular structure in the crystal also has to be one of the low-energy permitted conformations.…”
Section: A A6 Initio Nonempirical Modpot/vrddo Lcao-mo-scf Resultsmentioning
confidence: 99%
“…Ordinarily if there has been a crystal structure determined for a medium or large drug or biomolecule molecule, we initiate our quantum chemical calculations at the molecular geometry as determined in the crystal. Our prior experience [20,21] has indicated that for most molecules of this type, especially ones whose structure is composed primarily of ring skeletons, the major influence on molecular structure is intramolecular rather than crystal packing or intermolecular forces. The molecular structure in the crystal also has to be one of the low-energy permitted conformations.…”
Section: A A6 Initio Nonempirical Modpot/vrddo Lcao-mo-scf Resultsmentioning
confidence: 99%
“…We had also used that same concept of meshed pieces of structural conformation of different parts from different molecules to arrive at an initial guess for the structure of nalorphine [33], a narcotic agonist-antagonist (the N-ally1 derivative of morphine). The crystal structure of morphine had been determined [34], as had the crystal structure of naloxone [35].…”
Section: Methodsmentioning
confidence: 99%
“…rameters, the INDO procedure (a semirigorous quantum chemical method) seemed only to have been derived and parametrized by Pople [61] for molecules containing first-row atoms. Hence, we extended the INDO formulation by deriving the general INDO equations for d orbitals and obtaining the necessary parameters for secondrow atoms [62].…”
Section: B Quantum Chemical Calculationsmentioning
confidence: 99%